Anaphylaxis in new European Resuscitation Council Guidelines 2021 - Alihodzić, Hajriz (Journal Resuscitatio Balcanica, 2021)
Anaphylaxis is a potentially life-threatening allergic reaction. New guideline for treatment of anaphylaxis is presented in European Resuscitation Council Guidelines 2021: Cardiac arrest in special circumstances. There are no major changes. This guideline is specific for the initial treatment of adult patients with anaphylaxis or suspected anaphylaxis by clinician. Adrenaline is the most important drug for the treatment of anaphylaxis and the first line of treatment
Keywords: anaphylaxis; guidelines; adrenaline